2018
DOI: 10.1063/1.4996551
|View full text |Cite
|
Sign up to set email alerts
|

First-principles studies of electronic, transport and bulk properties of pyrite FeS2

Abstract: We present results from first principle, local density approximation (LDA) calculations of electronic, transport, and bulk properties of iron pyrite (FeS2). Our non-relativistic computations employed the Ceperley and Alder LDA potential and the linear combination of atomic orbitals (LCAO) formalism. The implementation of the LCAO formalism followed the Bagayoko, Zhao, and Williams (BZW) method, as enhanced by Ekuma and Franklin (BZW-EF). We discuss the electronic energy bands, total and partial densities of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Transition metal dichalcogenides (TMDC’s) have gained extensive research interest in the field of material sciences due to their photocatalytic and high optical absorption which are beneficial for the development of high power photovoltaic solar cells 1 . Among the members of TMDCs, pyrite FeS 2 (p-FeS 2 ) looks promising not only because of its remarkable optical absorption coefficient (α≈10 5 cm −1 in visible energy region) and photocurrent quantum efficiency (> 90%) 2 , 3 , but also due to its diverse features such as, suitable energy band gap ~ 0.95 eV, nontoxicity, cost-effectiveness and abundance 4 6 in nature. Despite, several research works 7 – 9 have reported suboptimal photovoltaic performance of p-FeS 2 due to its low band gap.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal dichalcogenides (TMDC’s) have gained extensive research interest in the field of material sciences due to their photocatalytic and high optical absorption which are beneficial for the development of high power photovoltaic solar cells 1 . Among the members of TMDCs, pyrite FeS 2 (p-FeS 2 ) looks promising not only because of its remarkable optical absorption coefficient (α≈10 5 cm −1 in visible energy region) and photocurrent quantum efficiency (> 90%) 2 , 3 , but also due to its diverse features such as, suitable energy band gap ~ 0.95 eV, nontoxicity, cost-effectiveness and abundance 4 6 in nature. Despite, several research works 7 – 9 have reported suboptimal photovoltaic performance of p-FeS 2 due to its low band gap.…”
Section: Introductionmentioning
confidence: 99%
“…This latter feature is common to FeS 2 compound, as well as the whole trend of the bands distribution which seems very similar (see refs. []). These similarities could be attributed to the fact that both compounds are isostructural, but more important are isoelectronic, that is, they have the same valence configuration.…”
Section: Resultsmentioning
confidence: 99%
“…We just recall that it is a semiconductor, with an indirect band gap and most of the experimental measurements give ≈0.9 eV (a good account of the computed and measured FeS 2 gap is reported in ref. []). In a previous work on Fe false( Mn , Ni false)normalS2 alloys, our GGA calculations gave Enormalg0.35 eV, much smaller than experimental value.…”
Section: Resultsmentioning
confidence: 99%
“…Bulk FeS 2 is a paramagnetic material with a band gap around 0.9 eV, which makes it a promising candidate for applications in the field of photovoltaic and photoelectron chemical cells [20][21][22]. FeS 2 is similar to MnSe 2 [14], which has been demonstrated to have high-temperature ferromagnetism down to monolayers whereas their bulk counterparts are low-temperature antiferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%